Single-cell RNA sequencing reveals cellular diversity and gene expression dynamics in maize root development - Bian, Jianwen; Zhuang, Zelong; Tang, Rui; Ta, Wanling; Ren, Zhenping; Peng, Yunling (Frontiers in Plant Science, 2025)
IntroductionRoots are essential for plant growth, functioning in nutrient and water uptake and anchorage.MethodsTo elucidate the molecular basis of maize root development at single-cell resolution, single-cell RNA sequencing (scRNA-seq) was performed on maize root tips.ResultsThis analysis identified nine cell types and ten transcriptionally distinct clusters based on marker and cluster-specific gene expression. Cyclin gene profiling revealed M-phase enrichment across most root tissues, indicating active cell division in the meristem. Further investigation uncovered cell-type expression patterns of hormone-related genes in maize roots, which diverged from those observed in A. thaliana and rice. Pseudotime analysis reconstructed the developmental trajectory from early to mature cortex, revealing candidate regulators of cell fate determination. Weighted gene co-expression network analysis (WGCNA) identified Zm00001d021775 (sugar transport protein STP4) as a hub gene in the mature cortex.DiscussionFunctional inference suggests STP4 promotes early seedling growth by facilitating glucose transport into glycolysis and the TCA cycle. These findings provide a high-resolution map of transcriptional landscapes in maize roots, offering new insights into cellular heterogeneity, developmental regulation, and potential molecular targets for enhancing root function and crop resilience.